2018
DOI: 10.1089/acm.2018.0030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acupuncture or Massage on Health-Related Quality of Life of Hemodialysis Patients

Abstract: Use of complementary therapies such as massage and acupuncture during HD may contribute toward improvement of HR-QOL and thus should be considered when addressing overall health status of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…The application of TCM and acupuncture concepts in the field of nephrology has been increasingly described in recent research [ 12 ]. Kim et al (2011) studied patients undergoing hemodialysis receiving acupuncture treatment for some of their symptoms, and acupuncture seemed to be feasible and safe for symptom management [ 13 ]; Bullen et al (2018) have concluded that acupuncture during HD may contribute toward the improvement of health-related QoL [ 14 ]; Yu et al (2017) evaluated the feasibility effect of acupuncture on renal function in patients with CKD and results suggest reduced creatinine levels and increased GFR [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The application of TCM and acupuncture concepts in the field of nephrology has been increasingly described in recent research [ 12 ]. Kim et al (2011) studied patients undergoing hemodialysis receiving acupuncture treatment for some of their symptoms, and acupuncture seemed to be feasible and safe for symptom management [ 13 ]; Bullen et al (2018) have concluded that acupuncture during HD may contribute toward the improvement of health-related QoL [ 14 ]; Yu et al (2017) evaluated the feasibility effect of acupuncture on renal function in patients with CKD and results suggest reduced creatinine levels and increased GFR [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The measurement of fatigue include Piper Fatigue Scale [17], Novel Fatigue Scale for Hemodialysis [18]; Fatigue Severity Scale [19][20][21], Fatigue Scale [22]; Rothen Fatigue Scale [23], and visual analog scale [24]. Quality of life were assessed using PROMIS [18,25,26] and KDQOL-SF 3 [19][20][21][22][23][24][27][28][29][30].…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…Complementary and integrative interventions using massage were used in three studies and show a significant reduced of fatigue [20,21,26]. Previous review showed significant effect of massage in reducing fatigue of patients with cancer [33].…”
Section: Characteristics Of Samplesmentioning
confidence: 99%
“…Physical therapy or exercise-based interventions have been successful in improving pain in the general population [41]. Few studies of exercise, physical therapy, yoga, or acupuncture in patients with kidney disease have included pain as an outcome but show promising results [42][43][44][45]. Given that non-pharmacological interventions are generally safe, further research should test the effectiveness, feasibility and acceptability of them for patients with kidney disease.…”
Section: Non-pharmacologic Approachesmentioning
confidence: 99%